Erchen decoction combined with Sanziyangqin decoction for chronic obstructive pulmonary disease: A protocol for systematic review and meta-analysis. Issue 40 (2nd October 2020) - Deng, Lu; Zhang, Xinyue; Dong, Yan; Wang, Lizhen; Chen, Keling; Zheng, Meiling; Yang, Zidanqing; Tang, Hui; Liao, Wenhao; Shi, Qunfeng
Abstract: Introduction: chronic obstructive pulmonary disease (COPD) is 1 of the leading causes of morbidity and mortality worldwide; its economic and social burdens are substantial and increasing. Recent years, an increasing number of study has shown the promising advantage of Erchen decoction (ECD) combined with sanziyangqin decoction (SZYQD) in treating COPD. However, due to the lack of evidence, there is no specific method or suggestion, so it is necessary to provide a protocol for a systematic review on ECD combined with SZYQD for COPD and provide effective evidence for further clinical use. Methods and analysis: We will conduct a Computerized literature searches in the following databases: PubMed, MEDLINE, EMBASE, Cochrane Library, China national information network, China biomedical literature database (CBM), Chinese Scientific Journals Database and wanfang database, from their inception to June 2020, without restrictions of language. Study selection, data collection, and evaluation of the quality of evidence will be performed by 2 researchers independently, risk of bias of the meta-analysis will be evaluated based on the Cochrane Handbook for Systematic Reviews of Interventions. All data analysis will be conducted by data statistics software Review Manager V.5.3. and Stata V.12.0. Results: This study will systematically evaluate the effectiveness and safety of ECD combined with SZYQD for COPD. The results will be published in a peer-reviewed journal. Conclusion: This study will provide evidence from the current published RCTs of whether ERD combined with SZYQD is an effective and safe intervention for COPD. Ethics and dissemination: This study is a systematic review, the outcomes are based on the published evidence. In this study, no individual data from participants will be involved, so ethics approval is not required. Open Science Framework(OSF)registration number: August 19, 2020; osf.io/zxm24.